2022
DOI: 10.3390/biom13010013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and a Breath Sensor Identify Acetone as a Biomarker for Heart Failure

Abstract: Background: Multi-omics delivers more biological insight than targeted investigations. We applied multi-omics to patients with heart failure with reduced ejection fraction (HFrEF). Methods: 46 patients with HFrEF and 20 controls underwent metabolomic profiling, including liquid/gas chromatography mass spectrometry (LC-MS/GC-MS) and solid-phase microextraction (SPME) volatilomics in plasma and urine. HFrEF was defined using left ventricular global longitudinal strain, ejection fraction and NTproBNP. A consumer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Indeed, in a study of non-ischemic HF patients, exhaled acetone levels, which were correlated with blood KB levels, were associated with higher NYHA class and higher BNP ( 26 ). In a study of 45 patients with HF, higher KB levels were correlated with a lower EF ( 2 ), while another study of 46 patients with HF with reduced EF found higher levels of acetone among HF patients compared with controls ( 27 ). However, we observed no cross-sectional association between KB and EF categories after controlling for several potential confounding factors, indicating that our findings surrounding KB correlates apply to the entire spectrum of the HF syndrome.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, in a study of non-ischemic HF patients, exhaled acetone levels, which were correlated with blood KB levels, were associated with higher NYHA class and higher BNP ( 26 ). In a study of 45 patients with HF, higher KB levels were correlated with a lower EF ( 2 ), while another study of 46 patients with HF with reduced EF found higher levels of acetone among HF patients compared with controls ( 27 ). However, we observed no cross-sectional association between KB and EF categories after controlling for several potential confounding factors, indicating that our findings surrounding KB correlates apply to the entire spectrum of the HF syndrome.…”
Section: Discussionmentioning
confidence: 97%
“…A study of 615 HF patients found that patients with high AcAc concentrations (≥ 35 μM) were at a small but detectable increased risk of all-cause mortality ( 36 ). Several studies have found an association between higher breath acetone levels and HF ( 26 , 27 , 33 , 37 ). Elevated levels of exhaled breath acetone have been reported to be an independent predictor of mortality in HF with reduced EF ( 25 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Acetone is a ketone body that is produced primarily in the liver during fasting and which has been associated with several cardiometabolic conditions including heart failure 55 and diabetes 56 in biochemical and epidemiological studies. In the GWAS, we identified associations for acetone at ten loci (only one associated locus— APOA5 —was identified in the previous NMR GWAS meta-analysis 4 ), and Mendelian randomization yielded 20 robust associations (Fig.…”
Section: Mendelian Randomizationmentioning
confidence: 99%
“…25,49 HF is a modestly ketotic state recognized by an increase in exhaled acetone and circulating ßOHB in human patients. [49][50][51][52][53][54] Given that cardiac uptake of ketone bodies is proportional to circulating concentrations, augmented hepatic ketogenesis is a likely contributor to increased cardiac utilization in HF via increased supply (Figure 2). 25,27 Extraction of ßOHB proportional to supply is increased in patients with reduced LVEF.…”
Section: Ketone Metabolism In the Hypertrophied And Failing Heart Car...mentioning
confidence: 99%